EFFICACY OF INTEGRATIVE SELF-REFLECTION INTERVENTIONS ON THE SELF-COMPASSION OF ADULTS WITH SYMPTOMS OF DEPRESSION - Afzal, Tabinda; Ahmad, Kiran Bashir (Journal of Pakistan Psychiatric Society, 2023)
Objective: The purpose of the research was to explore the impact of an integrated approach to self-reflections by combining the interventions from Naikan Therapy and Expressive Arts therapy on adults with symptoms of depression. It was hypothesized that after the successful completion of ten bi-weekly psychotherapeutic sessions over a period of 7 weeks (including pre and post assessment), participants would have increased levels of self-compassion compared to the pre-test levels. Research Design: The present research is a quasi-experimental research design. A total of eleven participants within the age range of 18-40 were included in the research using purposive sampling. Place and Duration of the Study: 1 year, at Bahria University, Karachi Campus Participants and Methods: Only participants who were experiencing symptoms of depression, between the age range of 18-40 and at least a 12th grade education level was included in the research. In addition to the Informed Consent Form, Demographic Information Form, Siddiqui Shah Scale of Depression (Siddiqui and Shah, 1997) and Self Compassion Scale (Neff, 2003) were used to assess the level of depressive symptoms and self-compassion of the participants before and after the intervention. Statistical Package for Social Science (SPSS) 22.0 was used for analysis and a paired sample t-test was conducted to see the differences between the pretest and posttest of the participants. Results: Results indicated a significant increase in the levels of self-compassion from pretest (M=57, SD=6.67) to posttest (M=102, SD=10.09) conditions; t (10) = -1.45, P<0.05. Conclusion: Integrative psychotherapies have been found to be effective in increasing awareness, improving self-awareness, improving mindfulness, and reducing self-critical thinking. Overall, these potential implications suggest that it may be an integrative form of therapy for individuals struggling with depression.